Effectiveness of stress release geometries on reducing residual stress in electroforming metal microstructure. (19th February 2018) - Song, Chang; Du, Liqun; Zhao, Wenjun; Zhu, Heqing; Zhao, Wen; Wang, Weitai
Abstract: Micro electroforming, as a mature micromachining technology, is widely used to fabricate metal microdevices in micro electro mechanical systems (MEMS). However, large residual stress in the local positions of the micro electroforming layer often leads to non-uniform residual stress distributions, dimension accuracy defects and reliability issues during fabrication of the metal microdevice. To solve this problem, a novel design method of presetting stress release geometries in the topological structure of the metal microstructure is proposed in this paper. First, the effect of stress release geometries (circular shape, annular groove shape and rivet shape) on the residual stress in the metal microstructure was investigated by finite element modeling (FEM) analysis. Two evaluation parameters, stress concentration factor K T and stress non-uniformity factor δ were calculated. The simulation results show that presetting stress release geometries can effectively reduce and homogenize the residual stress in the metal microstructures were measured metal microstructure. By combined use with stress release geometries of annular groove shape and rivet shape, the stress concentration factor K T and the stress non-uniformity factor δ both decreased at a maximum of 49% and 53%, respectively. Meanwhile, the average residual stress σ avg decreased at a maximum of 20% from −292.4 MPa to −232.6 MPa. Then, micro electroforming experiments were carried out corresponding to the simulation models. The residual stresses in the metal microstructures were measured by micro Raman spectroscopy (MRS) method. The results of the experiment proved that the stress non-uniformity factor δ and the average residual stress σ avg also decreased at a maximum with the combination use of annular groove shape and rivet shape stress release geometries, which is in agreement with the results of FEM analysis. The stress non-uniformity factor δ has a maximum decrease of 49% and the average residual stress σ avg has a maximum decrease of 37% from −257.0 MPa to −162.0 MPa.